2022
DOI: 10.3390/s22218510
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Skin-Electrode Contact Impedance on Material and Skin Hydration

Abstract: Dry electrodes offer an accessible continuous acquisition of biopotential signals as part of current in-home monitoring systems but often face challenges of high-contact impedance that results in poor signal quality. The performance of dry electrodes could be affected by electrode material and skin hydration. Herein, we investigate these dependencies using a circuit skin-electrode interface model, varying material and hydration in controlled benchtop experiments on a biomimetic skin phantom simulating dry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…The term traditionally applies to the electrolyte gel, but for woven textile electrodes there is no electrolyte gel. Without electrolyte the contact pressure against the skin, and the moisture between skin and electrode become much more important [ 12 , 23 , 27 ]. A short period of time after application, a minuscule layer of perspiration accumulates between the epidermis and the conductive yarn [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term traditionally applies to the electrolyte gel, but for woven textile electrodes there is no electrolyte gel. Without electrolyte the contact pressure against the skin, and the moisture between skin and electrode become much more important [ 12 , 23 , 27 ]. A short period of time after application, a minuscule layer of perspiration accumulates between the epidermis and the conductive yarn [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of textile electrodes, initially there is no electrolyte. However, after a few minutes minuscule amounts of perspiration accumulate and behave the same as a thin layer of electrolyte, meaning from a modeling perspective they have the same circuit structure as wet electrodes when used for wellness monitoring [ 12 , 18 , 26 ]. The cumulative impedance of these circuit elements across the interface, defined as , is expressed in the Laplace domain in Equation ( 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Innately flexible and conformable e-tattoos can record bioelectric signals at various anatomical locations, providing valuable information about cardiac, muscular, and neural activities. ,, The evolution of e-tattoos has been primarily motivated by the imperative to reduce the electrode–skin contact impedance and artifacts from movements and environmental changes, while simultaneously improving comfort during long-term wear. Lowering the electrode–skin contact impedance can improve the signal-to-noise ratio. , Metals with a high innate conductivity (e.g., noble metals), ,, conducting polymers with a high ionic mobility and a high charge transfer rate (e.g., PEDOT:PSS), , and carbon nanomaterials with both good conductivity and large surface area (e.g., graphene, ,, CNTs), and 2D dichalcogenides with ultrathin thickness have been used to reduce the contact impedance of the electrodes on the skin. Minimizing artifacts is crucial for accurate diagnostic monitoring because these artifacts can be falsely interpreted as signals or even mask the actual bioelectric signal.…”
Section: E-tattoo Sensorsmentioning
confidence: 99%
“…CC is a non-invasive technology that applies an electric field, and two skin electrodes are aimed at the treatment site. Therefore, electrical energy is induced from one electrode to the other electrode through frequency changes to stimulate the treatment site and achieve the purpose of treatment [ 24 , 25 , 26 ]. Studies have reported that a PEMF, DC, and CC have therapeutic effects on osteoporosis.…”
Section: Introductionmentioning
confidence: 99%